Muscular forces affect the glycosaminoglycan content of joint cartilage: Unloading in human volunteers with the HEPHAISTOS lower leg orthosis. (2014) - Ganse, Bergita; Zange, Jochen; Weber, Tobias; Pohle-Fröhlich, Regina; W Johannes, Bernd; Hackenbroch, Matthias; Rittweger, Jörn; Eysel, Peer; Koy, Timmo
Abstract : Background and purpose — Unloading alters the thickness of joint cartilage. It is unknown, however, to what extent unloading leads to a loss of glycosaminoglycans (GAGs) in the cartilage tissue. We hypothesized that muscle forces, in addition to axial loading, are necessary to maintain the joint cartilage GAG content of the knee and the upper and lower ankle. Patients and methods — The HEPHAISTOS orthosis was worn unilaterally by 11 men (mean age 31 (23–50) years old) for 56 days. The orthosis reduces activation and force production of the calf muscles while it permits full gravitational loading of the lower leg. MRI measurements of the knee and ankle were taken before the intervention, during the intervention (on day 49), and 14 days after the end of the intervention. Cartilage segmentation was conducted semiautomatically for the knee joint (4 segments) and for the upper (tibio-talar) and lower (subtalar) ankle joints (2 segments each). Linear mixed-effects (LME) models were used for statistical analysis. Results — 8 volunteers completed the MRI experiment. In the lower ankle joint, differences in ΔT1 were found between the end of the intervention and 14 days after (p = 0.004), indicating a decrease in GAG content after reloading. There were no statistically significant differences in ΔT1 values in the knee and upper ankle joints. Interpretation — Our findings suggest that in addition to gravitational load, muscular forces affect cartilage composition depending on the local distribution of forces in the joints affected by muscle contraction.